Insiders-outsiders, transparency and the value of the ticker - Giovanni Cespa; Thierry Foucault (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
We consider a multi-period rational expectations model in which risk-averse investors differ in their information on past transaction prices (the ticker). Some investors (insiders) observe prices in real-time whereas other investors (outsiders) observe prices with a delay. As prices are informative about the asset payoff, insiders get a strictly larger expected utility than outsiders. Yet, information acquisition by one investor exerts a negative externality on other investors. Thus, investors' average welfare is maximal when access to price information is rationed. We show that a market for price information can implement the fraction of insiders that maximizes investors' average welfare. This market features a high price to curb excessive acquisition of ticker information. We also show that informational efficiency is greater when the dissemination of ticker information is broader and more timely.
urn:nbn:de:hebis:30-62189
Keywords: G10; G12; G14; 330; Market Data Sales; Latency; Transparency; Price Discovery; Hirshleifer Effect; Kapitalanlage; Transaktionskosten; Information; Insiderhandel; Wohlfahrtseffekt; Rationale Erwartung; Theorie